Development of Web-App using Agile Scrum Method at PT. Stechoq Robotika Indonesia - Mufreni, Sadr Lufti; Mushawwir, Ahmad (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The increasing number of Jaminan Kecelakaan Kerja (JKK) claims over the past five years underscores the urgency of enhancing workplace safety measures. One possible solution is the adoption of Automated Guided Vehicles (AGVs) to streamline warehouse operations and minimize the risks associated with manual handling. In this study, the AGV is owned by the stakeholder, PT. Stechoq Robotika Indonesia (STECHOQ), which is responsible for AGV customization and the development of its control system through a web-based application. The web-app was developed using ReactJS, TypeScript, and Tailwind CSS, adopting the Agile Scrum methodology The web-app development followed a two-sprint approach, with each sprint lasting one week. A total of six key features were implemented Login, Dashboard, Station Management, AGV Management, Task Management, and Robot Control. Iterative Black Box Testing was conducted on these six features throughout both sprints, confirming their successful operation without any issues. Additionally, this study modified the Agile Scrum methodology by merging the sprint retrospective with the sprint review phase, enhancing efficiency while aligning with the existing workflow. The objective of this study is to develop a web-based application capable of controlling the stakeholder's AGV.